Operation of spiritual values ​​as a philosophical and religious studies problem - Конотоп, Л.Г.; Проценко, Е.Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
Article is devoted to philosophical and religious analysis of problems of cultural values.